Data-Independent Acquisition Proteomics Unravels the Effects of Iron Ions on Coronatine Synthesis in Pseudomonas syringae pv. tomato DC3000 - He, Yan; Yu, Sha; Liu, Shaojin; Tian, Hao; Yu, Chunxin; Tan, Weiming; Zhang, Jie; Li, Zhaohu; Jiang, Feng; Duan, Liusheng (Frontiers in Microbiology, 2020)
Coronatine (COR) is a new type of plant growth regulator that is produced by Pseudomonas syringae pathovars and plays an important role in modulating plant growth, development, and tolerance to multiple stresses. However, the factors affecting COR production are not very clear. In this study, the effects of FeCl3 on COR production were researched. The data-independent acquisition (DIA) approach, which is a proteomic quantitative analysis method, was applied to quantitatively trace COR production and proteomic changes in P. syringae pv. tomato DC3000 under different FeCl3 culture conditions. The results showed that COR production increased with the addition of FeCl3 and that there was significant upregulation in the expression of proteins related to COR synthesis and regulation. In addition, FeCl3 also affected the expression of related proteins involved in various metabolic pathways such as glycolysis and the tricarboxylic acid cycle. Moreover, various precursors such as isoleucine and succinate semialdehyde, as well as other related proteins involved in the COR synthesis pathway, were significantly differentially expressed. Our findings revealed the dynamic regulation of COR production in response to FeCl3 at the protein level and showed the potential of using the DIA method to track the dynamic changes of the P. syringae pv. tomato DC3000 proteome during COR production, providing an important reference for future research on the regulatory mechanism of COR biosynthesis and theoretical support for COR fermentation production.